ANALISA PENGALIHAN PENGELOLAAN ATAS ASSET PEMERINTAH KOTA MEDAN KEPADA PIHAK KEDUA (STUDI KASUS : HAK PENGELOLAAN PASAR PERINGGANMEDAN) - RATNA SITEPU (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhammad Yamin2. Suhaidi3. Faisal Akbar Nasution The right of management is the right of the State’s control which part of the authority is transferred to the holder. The Medan Municipal Government has a great deal of assets which management are transferred to the other parties; one of the assets is Pasar Peringgan. The land and the buildings of Pasar Peringgan are owned by the Medan Municipal Government which management is transferred to the second party. PT. Triwira Loka Jaya (TLJ), embodied in the Build Operate Transfer (BOT) contract within 20 (twenty) years, commencing from May 23, 1996 until May 23, 2016. The research used juridical normative and descriptive analytic method. Secondary data were obtained from primary, secondary, and tertiary legal materials.Keywords: Transfer, Asset Management, the Right of Management